COMPARATIVE EFFICACY OF NPK FERTILIZER AND POULTRY DROPPINGS ON THE GROWTH AND YIELD OF AMARANTHUS HYBRIDUS L. - Victor Onuche IKANI; Bawa Gambo ZAKARI; Zubairu Gaddafi JIMETA; Ahmad IDI (Journal of Plant Development)
The persistent reduction in soil fertility as a result of continuous cultivation of the soil has become a problem to vegetable farmers, both inorganic and organic fertilizers have been recommended as good sources of nutrients. This study sought to compare the performance of NPK (15:15:15) and poultry manure at different application rate on the growth and yield of Amaranthus hybridus. The experiment was done in duplicate and laid out using a Randomized Complete Block Design (RCBD) with each plot measuring 1.2 m by 1.2 m. The plant height (117 cm), leaf length (22.70 cm), leaf width (14.60 cm), leaf area index (12.10 cm2), fresh weight (387.58 g) and dry weight (54.20 g) were significantly (P<0.05) higher in plant with application rate of 15 g poultry dropping compared to NPK fertilizer and the control. Poultry droppings (15 g) is more efficient to be used by farmers for optimum growth and yield of A. hybridus.